2024
DOI: 10.1186/s12885-024-12545-7
|View full text |Cite
|
Sign up to set email alerts
|

It’s about time: mitigating cancer-related cognitive impairments through findings from computational models of the Wisconsin Card Sorting Task

Darren Haywood,
Frank D. Baughman,
Evan Dauer
et al.

Abstract: Background Many cancer survivors experience cancer-related cognitive impairment (CRCI), often with significant negative consequences across various life domains. Emerging evidence suggests that allowing additional time to process information before acting may be a useful strategy for those with CRCI to mitigate some of its impacts. The Wisconsin Card Sorting Task (WCST), a measure of general cognition, has shown that for some cancer survivors, longer task completion time facilitates similar tas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Relatedly, mental health challenges are consistently linked with cognitive dysfunction across populations [ 8 , 9 , 10 , 11 , 12 ], and cancer survivors are at a greater risk of experiencing mental ill-health [ 13 , 14 , 15 , 16 , 17 ]. Therefore, it has been suggested that mental health challenges and CRCI may have a bidirectional functional relationship, each contributing toward the development and maintenance of the other [ 4 , 18 ]. Irrespective of the aetiology of CRCI, its effects on the overall well-being of individuals with cancer appear to affect multiple aspects of their lives [ 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Relatedly, mental health challenges are consistently linked with cognitive dysfunction across populations [ 8 , 9 , 10 , 11 , 12 ], and cancer survivors are at a greater risk of experiencing mental ill-health [ 13 , 14 , 15 , 16 , 17 ]. Therefore, it has been suggested that mental health challenges and CRCI may have a bidirectional functional relationship, each contributing toward the development and maintenance of the other [ 4 , 18 ]. Irrespective of the aetiology of CRCI, its effects on the overall well-being of individuals with cancer appear to affect multiple aspects of their lives [ 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%